Cybersecurity als Unternehmensleitungsaufgabe (Volume 2) - Bittner, Marc-Philipp; Guntermann, Anabel; Müller, Christoph Benedikt; Rostam, Darius (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Cybersecurity is a central challenge for many companies. On the one hand, companies have to protect themselves against cyberattacks; on the other hand, they have special obligations towards third parties and the state in critical infrastructures or when dealing with personal data. These responsibilities converge with company management. This volume examines the duties and liability risks of management in connection with cyber security from the perspective of corporate, constitutional and labour law. The volume is based on a conference of the same name, which took place in cooperation with the Friedrich Naumann Stiftung für die Freiheit on 23 and 24 October 2020 at Bucerius Law School in Hamburg. With contributions by Andreas Beyer, Marc Bittner, Alexander Brüggemeier, Anabel Guntermann, Katrin Haußmann, Dennis-Kenji Kipker, Christoph Benedikt Müller, Isabella Risini, Darius Rostam, Sarah Schmidt-Versteyl and Gerald Spindler.